الكَفاءة الاقتصادية لإنتاج الفول السُّوداني في السَّاحل السُّوري - جحجاح, محسن; ابراهيم, حلا (Latakia University Journal -Biological Sciences Series, 2018)
أُجري هذا البحث في السَّاحل السُّوري(محافظتي اللَّاذقيَّة وطرطوس), وهَدفَ إلى التعرف على الكفاءة الاقتصادية لزراعة محصول الفول السُّوداني , من خلال تطبيق مقاييس الكفاءة الاقتصادية للزراعة وأهم مؤشراتها. وقد تمَّ الإيفاء بمتطلبات البحث, مما يحتاجه من بيانات, اعتماداً على استمارة استبانة, وُزعت عشوائياً على (377) مزارعاً من مزارعي المحصول, في منطقة الدِّراسة, وتمَّ اختيار (20) قرية, تابعة لأربع مناطق (اللاذقية, جبلة, طرطوس, بانياس) في المحافظتين المذكورتين, خلال الموسم الزِّراعي (2016-2017). نُفِذَ البحث اعتماداً على أسعار 2017, ومقارنتها بأسعار 2010, حيث تمَّ اعتماد الأسعار والتكاليف والأجور وقت إنفاقها، أي من وقت إعداد الأرض وتحضيرها للزراعة وصولاً إلى الإنتاج والتسويق. وأظهرت نتائج الدِّراسة أن جميع المزارعين ,حققوا عوائد إيجابية, وفقاً للمعايير الاقتصادية المستخدمة . وأن محصول الفول السُّوداني له ريعيَّة اقتصاديَّة جيدَّة ويُحقق الآتي: 1- الناتج الإجمالي ل.س/ دونم/سنة =295000 ل.س/دونم/سنة. 2- التكاليف الإنتاجية الإجمالية ل.س/ دونم/سنة =216862 ل.س/دونم/سنة. 3- صافي الدخل المزرعي ل.س/ دونم/ سنة =94310 ل.س/دونم/سنة. 4- الربح ل.س /دونم /سنة = 78138 ل.س/دونم/سنة. 5- معامل الربحية : أ‌- معامل الربحية بالقياس إلى التكاليف الإنتاجية= 55.13 % ب‌- معامل الربحية بالقياس إلى رأس المال المستثمر =36.18%. The research was carried out in the Syrian coast (Lattakia and Tartous governorates). The aim was to identify the economic efficiency of peanut growing by applying the economic efficiency measures for agriculture and its most important indicators. The research requirements, based on a questionnaire, were randomly distributed to( 377) crop growers in the study area. Twenty villages were selected from four regions (Lattakia, Jablah, Tartous, Banias) In the two governorates mentioned above, during the agricultural season (2016-2017). The research was carried out based on the prices of 2017 and compared with the prices of 2010, where prices, costs and wages were adopted at the time of their expenditure, from the time the land was prepared and prepared for agriculture to production and marketing. The results of the study showed that all farmers achieved positive returns, according to economic criteria used. And that the peanut crop has a good economic profitability and achieve the following: 1. GDP (SP /dunum / year) SP =295000SP/dunum/year. 2. The total production costs (SP dunum / year) = 216862 SP/dunum/year. 3. Net farm income per dunum (SP dunum / year) = 94310 SP/dunum/year. 4. Profit from dunum (SP dunum / year) = 78138 SP/dunum/year. 5. profitability coefficient: A coefficient of profitability compared to the production costs = 55.13%. B. earnings multiple relative to invested capital = 36.16%.